2017
DOI: 10.18203/2320-1770.ijrcog20170469
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy as a diagnostic tool in evaluation of female factors in infertility

Abstract: Background: Infertility leads to considerable personal suffering and disruption of family life. According to United Nations "Reproductive health is a state of complete physical mental and social well-being and not merely the absence of disease or infirmity in all matters relating to the reproductive system and to its functions and processes". The objective of present study was to find out different causes of female infertility with diagnostic laparoscopy and their comparative frequency in primary and secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Various studies like that of Shetty et al and Krishna C et al have shown that there is rise in age at which women present with infertility. 4,6 In present study, 3 (3.7%) patients of primary infertility and 6 (26.1%) of secondary infertility were of age >30 years. Because of the decline in fertility and the increased time to conception that occurs after the age of 30, women >30 years of age should be referred for infertility work-up after 6 months of trying to conceive.…”
Section: Discussionsupporting
confidence: 44%
“…Various studies like that of Shetty et al and Krishna C et al have shown that there is rise in age at which women present with infertility. 4,6 In present study, 3 (3.7%) patients of primary infertility and 6 (26.1%) of secondary infertility were of age >30 years. Because of the decline in fertility and the increased time to conception that occurs after the age of 30, women >30 years of age should be referred for infertility work-up after 6 months of trying to conceive.…”
Section: Discussionsupporting
confidence: 44%
“…Laparoscopy is a mandatory procedure for full assessment of the infertile couple 1 It is widely accepted that infertility is a common medical problem. The role of laparoscopy in the diagnosis of primary and secondary infertility is established beyond any doubt 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic laparoscopy is generally not a part of initial infertility evaluation; however, number of reports have shown that it is effective procedure for evaluation of long term infertility 1 .…”
mentioning
confidence: 99%
See 2 more Smart Citations